PERBANDINGAN METODE EXPONENTIAL SMOOTHING DALAM PERAMALAN JUMLAH PEMBELIAN BAHAN BAKU PRODUK PINTU PADA PT.X - Amel, Amelia Purbaningtyas; Ernawati, Dira (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2025)
The industrial sector is a productive component for economic development in Indonesia because it has the ability to encourage economic growth. PT X is one of the companies that uses a make to order system. However, in procuring raw materials, PT X does not use forecasting as a basis for providing raw materials. Raw materials will be ordered when the stock in the warehouse reaches a predetermined minimum limit so that raw material shortages often occur when there are product fluctuations. This problem causes production delays and will affect operational efficiency. To follow up on problems that occur, forecasting techniques need to be used as a basis for procuring raw materials. The aim of conducting company forecasting is to increase profitability because raw material purchases are carried out in a planned manner which will open up opportunities to get lower raw material prices through bulk purchases. The forecasting methods that will be used are the single exponential smoothing, double exponential smoothing, and triple exponential smoothing methods. These three methods will be compared in order to get the best forecasting results for each raw material. Based on the calculations and analysis carried out, the Triple Exponential Smoothing method shows the smallest error rate for MDF, hardwood and softwood raw materials with MAPE values ​​of 69.86; 28.51; 35.11. Meanwhile, for plywood raw materials, the method that shows the smallest error rate is the Double Exponential Smoothing method with a MAPE value of 62.38.